The official (ISC)2 guide to the SSCP CBK - Gordon, Adam; Hernandez, Steven (Sybex, 2016)
The (ISC) 2 Systems Security Certified Practitioner (SSCP) certification is one of the most popular and ideal credential for those wanting to expand their security career and highlight their security skills. If you are looking to embark on the journey towards your (SSCP) certification then the Official (ISC) 2 Guide to the SSCP CBK is your trusted study companion. This step-by-step, updated 3 rd Edition provides expert instruction and extensive coverage of all 7 domains and makes learning and retaining easy through real-life scenarios, sample exam questions, illustrated examples, tables, and best practices and techniques. Endorsed by (ISC)² and compiled and reviewed by leading experts, you will be confident going into exam day. Easy-to-follow content guides you through Major topics and subtopics within the 7 domains Detailed description of exam format Exam registration and administration policies Clear, concise, instruction from SSCP certified experts will provide the confidence you need on test day and beyond . Official (ISC) 2 Guide to the SSCP CBK is your ticket to becoming a Systems Security Certified Practitioner (SSCP) and more seasoned information security practitioner.
Includes bibliographical references. - Online resource; title from title page (Safari, viewed August 29, 2016)
Keywords: Electronic data processing personnel -- Certification; Telecommunications engineers -- Certification; Computer security -- Study guides -- Examinations; Computer networks -- Study guides -- Security measures -- Examinations; Sécurité informatique; Examens; Guides de l'étudiant; Réseaux d'ordinateurs; Sécurité; Mesures; Examens; Guides de l'étudiant; Computer networks; Security measures; Examinations; Computer security; Examinations; Electronic data processing personnel; Certification; Telecommunications engineers; Certification; Study guides